Assessment of Inventory and Transportation Collaboration in a Logistics Marketplace - Shahid, Saif Mohammad (2020)
A Master of Science thesis in Engineering Systems Management by Saif Mohammad Shahid entitled, “Assessment of Inventory and Transportation Collaboration in A Logistics Marketplace”, submitted in March 2020. Thesis advisor is Dr. Malick Ndiaye. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).